2014
DOI: 10.1007/s11250-014-0746-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics and trypanosome prevalence of Mursi cattle breed in the Bodi and Mursi districts of South Omo Zone, southwest Ethiopia

Abstract: The study was conducted to characterize the morphological features of Mursi cattle breed and to identify the species of trypanosome infecting the cattle and its prevalence in these traditionally managed cattle in the Bodi and Mursi pastoral communities. Cattle body description and measurements were made on 201 matured animals. Blood samples were collected from 409 animals into heparin-treated capillary tubes and were centrifuged to 12,000 rpm for 5 min to identify trypanosome species from the wet smeared buffy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
6
20
1
Order By: Relevance
“…These include horn shape and size (e.g. Ankole and Kuri cattle: [11,37,38] and coat colour (i.e Nguni) as shown in Figure 2. In addition to physical features, non-visible traits such as disease resistance, climatic stress resistance and productivity traits also differ among breeds.…”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%
See 1 more Smart Citation
“…These include horn shape and size (e.g. Ankole and Kuri cattle: [11,37,38] and coat colour (i.e Nguni) as shown in Figure 2. In addition to physical features, non-visible traits such as disease resistance, climatic stress resistance and productivity traits also differ among breeds.…”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%
“…In addition to physical features, non-visible traits such as disease resistance, climatic stress resistance and productivity traits also differ among breeds. These characteristics are largely the result of natural and human selection [38]. …”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%
“…Two locations, Mursi and Bodi areas, where the Mursi and Bodi pastoral communities live, respectively, were selected for this study. The two pastoral communities keep the Mursi cattle breed and share common territorial boundary and the locations also characterized by tsetse fly infested area, where trypanosome is prevalent (Terefe et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…The pastoralists prefer the breed due to its perceived relative trypanotolerance (that is, its ability to survive and produce under trypanosomosis challenge) in trypanosomosis epidemic areas (Terefe et al, 2015), where there is little veterinary services. The study reported here is part of a project, which designed to study phenotypic characterization and trypanosomosis prevalence in Mursi cattle breed in its production environment.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high gene flow and admixture between indigenous cattle breeds is one of the major contributing factors in threatening unique cattle breeds [27], [40]. In Borana area, pastoralists usually move to look for feed and water resources which leads the breed to be admixed with the surrounding small sized zebu in the watering and feeding points [47], [16]. Similarly, there is indiscriminate crossbreeding and high affinity of replacing Sheko cattle by other thoracic-humped zebu cattle which have good temperament [6], [31], [32], [34].…”
Section: High Rate Gene Flow and Genetic Dilution Among Indigenous Brmentioning
confidence: 99%